Perpendicular Strut Injection of Hyaluronic Acid Filler for Deep Wrinkles. Issue 11 (November 2015) - Mashiko, Takanobu; Kinoshita, Kahori; Kanayama, Koji; Feng, Jingwei; Yoshimura, Kotaro
Abstract : Summary: Although various injection techniques of hyaluronic acid (HA) filler for facial rejuvenation have been developed, correction of deep wrinkles/grooves, such as the nasolabial fold (NLF), with intradermal or subdermal injections remains difficult. We tested the intradermal HA injection method to place multiple HA struts by (1) inserting a small needle perpendicularly to the wrinkle and (2) injecting HA as intradermal struts with the skin fully stretched by the practitioner's fingers. The results of both NLFs in 10 patients suggest that this technique improves NLFs and maintain the effects more consistently than conventional techniques, although the effects of both methods were almost lost after 6 months. Selective and/or combined application of this technique may enhance the current approach to facial rejuvenation with dermal fillers. Abstract : Supplemental Digital Content is available in the text.